Correlation between Kupffer Cell Infiltration and Liver Parenchymal Cell Damages in Immunosuppressed Drugs-Induced Rats - Pargaputri, Agni Febrina; Wahjuningsih, Endah; Andriani, Dwi (Faculty of Medicine, Universitas Padjadjaran, 2024)
The liver is the largest organ in the body, composed of both parenchymal and non-parenchymal cells. Chemical substances and various drugs can induce liver injury and involve Kupffer cells which are non-parenchymal cells that release biologically active substances, promoting pathological processes. This study aimed to evaluate the correlation between the number of Kupffer cells and liver parenchymal cell damages in immunosuppressed, drug-induced rats. The study was conducted from July to December 2019 at the Oral Biology Laboratory of the Faculty of Dentistry and the Biochemical Laboratory of the Faculty of Medicine at Universitas Hang Tuah Surabaya. Twelve healthy male Wistar rats were divided into two groups: Healthy (H) and Immunosuppressed Drug-Induced (ID) groups. Immunosuppression was induced using dexamethasone (0.5 mg/day/rat), administered orally for 14 days, combined with tetracycline (1%/day/rat). Liver samples from all rats were examined for Kupffer cell count and parenchymal cell damages were assessed using a light microscope with 400x magnification. Results revealed a significant difference in the number of Kupffer cells and liver parenchymal cell damages between the H and ID groups (p<0.05). Pearson correlation analysis indicated a significant correlation between Kupffer cell number and parenchymal cell damages (p=0.000). Continuous administration of immunosuppressive drugs may activate Kupffer cells, leading to damage of liver parenchymal cells. In conclusion, the infiltration of Kupffer cells is associated with liver parenchymal cell damages, mediated by various factors in the immunosuppressed drug-induced rat model.